Raw Seismic Navigation Data from the Southern Ocean and Southeast Indian Ridge acquired during R/V Maurice Ewing expedition EW0114 (2001) (IEDA: Marine-Geo Digital Library, 2005)
This data set from the Southern Ocean and Southeast Indian Ridge was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW0114 conducted in 2001 (Chief Scientist: Dr. James Cochran). These data files are of UKOOA P2/94 format and include Seismic Navigation data that have not been processed. For this experiment, the primary navigation source files for seismic data processing are the Seismic ShotPoint Navigation data. Data were acquired as part of the project: The Effects of Changes in Mantle Temperature on Melt Supply and Crustal Accretion: An MCS Reflection and OBH Refraction Study of the Southeast Indian Ridge, and funding was provided by NSF grant: OCE99-11720. These data are cited by Baran et al., 2009.